CONTROL ORGANIZATION OF TECHNOLOGICAL PROCESSES OF RAILWAY STATIONS ON THE BASIS OF STATISTICAL METHODS - Kozachenko, D. M.; Hermaniuk, Y. N.; Manafov, E. K. (Science and Transport Progress, 2019)
Purpose. The article is aimed to develop statistical methods for monitoring the technological processes of railway stations` operation based on Stewhart charts. Methodology. The research is based on the methods of statistical quality control and the theory of railways operation. Findings. Existing methods for monitoring the implementation of technological processes of railway stations are focused on achieving quantitative indicators of their work while unconditionally fulfilling the necessary list of technological operations and observing train movement safety requirements. At the same time, the problem of monitoring compliance with quality indicators of railway stations` operation requires additional research. The main criterion for evaluating the quality of technological processes associated with the processing of trains, locomotives, cars, containers, cargoes, documents and information at railway stations is their duration. Considering that the time spent on processing these objects is random, it is proposed to use statistical methods, in particular, Stewhart charts, for monitoring and controlling the technological processes of the stations` operation. As an example, we discussed the processes of maintenance of freight train cars after departure and constructed Stewhart charts for Kleparov and Baladzhary stations. Operation analysis of both stations showed a significant influence of local conditions on the duration of train maintenance by departure, as well as significant deviations between its standard and actual duration. Originality. For the first time this paper proposed a method for controlling technological processes of railway stations based on the use of Stewhart control charts. Practical value. Application of the proposed method makes it possible, on the one hand, to adequately control the duration of technological processes and individual technological operations, which are usually random variables, and on the other hand, to evaluate the feasibility of implementing the norms established by technological processes. In addition, the organization at the stations of accumulating statistical information on the progress of technological processes will also significantly simplify the construction of adequate simulation models that take into account the stochastic nature of railway stations` functioning.